THE PBl AND PB1-F2 GENES OF THE INFLUENZA VIRUS A/H5N1 STRAIN (A/CKAaETNAM/HG4/2005) AND ITS COMPARATIVE ANALYSIS WITH THOSE ISOLATED DURING 2004 - 2007 EV THE MEKONG DELTA REGION - Vui, Trần Quang (Vietnam Journal of Biotechnology, 2011)
The  entire  PBl  gene  of  an  avian  influenza  isolate  collected  from  a  chicken  in  Hau  Giang  province (designated    as   A/CkA^ietnam/HG4/2005)   was   obtained,   completely    sequenced,    and   analyzed    for identity/homology  with those strains available during 2004 - 2007 in the Mekong Delta region. As results, the entire PBl  gene obtained fi:om the A/CkA^ietnam/HG4/2005(H5Nl) strain is 2274 bp, encoding for  the PBl polypeptide of 757 amino acids. The 2274 bp is the size of all the avian influenza A/H5N1 strains belonging to the Guangdong sublineage, invariable since the formation ofthe  clade 1.0 (1997). PBl  has  11 nucleotide and 5 amino  acid variations  in comparison  to those  isolated  in the  Mekong  Delta  region  during  2004  - 2007. The PB1-F2, enclaved  in the PBl  nucleotide frame  from  nucleotide  95 to 367, coding 90 amino acids. Asparagin amino acid (N) at the 66'  site in the PB1-F2 is unchanged in all the strains isolated in the Mekong Delta region during 2004 - 2007 so far in this study. The identity ofthe  PBl  gene of A/Ck/Vietnam/HG4/2005 is 97% for nucleotide at the lowest and 100% at the highest level; the homology is varied 98 - 99%»for amino acid (protein P&l) and 96 - 98% (protein PB1-F2). All 18 sUains isolated in the Mekong Delta region belong to clade  1.0 of the Guangdong sublineage.